Gluten-Free Products for Celiac Susceptible People - Rai, Sweta; Kaur, Amarjeet; Chopra, C. S. (Frontiers in Nutrition, 2018)
The gluten protein of wheat triggers an immunological reaction in some gluten-sensitive people with HLA-DQ2/8 genotypes, which leads to Celiac disease (CD) with symptomatic damage in the small intestinal villi. Glutenin and gliadin are two major components of gluten that are essentially required for developing a strong protein network for providing desired viscoelasticity of dough. Many non-gluten cereals and starches (rice, corn, sorghum, millets, and potato/pea starch) and various gluten replacers (xanthan and guar gum) have been used for retaining the physical-sensorial properties of gluten-free, cereal-based products. This paper reviews the recent advances in the formulation of cereal-based, gluten-free products by utilizing alternate flours, starches, gums, hydrocolloids, enzymes, novel ingredients, and processing techniques. The pseudo cereals amaranth, quinoa, and buckwheat, are promising in gluten-free diet formulation. Genetically-modified wheat is another promising area of research, where successful attempts have been made to silence the gliadin gene of wheat using RNAi techniques. The requirement of quantity and quality for gluten-free packaged foods is increasing consistently at a faster rate than lactose-free and diabetic-friendly foods. More research needs to be focused on cereal-based, gluten-free beverages to provide additional options for CD sufferers.